Process Optimization of DWC for Fatty Acid Fractionation using Taguchi Methods of Experimental Design - Mohamad Rizza, Othman; Umarul Imran, Amran; Gade Padu, Rangaiah (AIDIC Servizi, 2015)
Experimental design (ED) is a powerful technique for optimizing the performance of a process. Compared to a model-based optimization technique, ED does not require the development of mathematical formulation but nevertheless needs a good model or experimental setup and statistical analysis. This paper presents an ED based optimization approach of a dividing wall column (DWC) model for industrial oleochemical fatty acid fractionation. Taguchi method of ED will be used for the optimization of the control variables for efficient fractionation of fatty acid cuts, namely light-cut (LC), middle-cut (MC) and heavy-cut (HC). The DWC model was developed in Aspen Plus software using a rigorous four-column configuration. It is used to identify sensitive parameters, simulate experimental layout trials and results validation. The process is designed to achieve product purity of >99 mol.% LC and MC, and >90 mol.% for HC. A step-by-step approach to process optimization using Taguchi method is presented along with the statistical analysis results and their interpretation. The ED output will help in understanding the interaction between variables and their effects. With its simple, fast and non-tedious approach, ED using Taguchi method could prove its significance in improving the performance of fatty acid fractionation using DWC for possible industrial application.